DESAIN KONTROL ROBOT MANIPULATOR KAPASITAS 1.25 kgf - Sirojuddin Sirojuddin; Yudha Adigutama; Eko Arif Syaefudin; Mohamad Ilham Al Fatah (Jurnal Rekayasa Mesin, 2022)
A robotic manipulator is one type of popular industrial robot which has a shape and movement that resemble a human arm. Robotic Manipulator mainly consists of a base, arm, gripper, and control system. This research focused on the control aspect of robot manipulators to handle 1.25 kgf load through experiment as a model of the robot with inverse kinematics. The design of the robot control uses 5 degrees of freedom using a servo motor as its actuator to achieve an accurate and stable movement on its x, y, and z coordinates using a microcontroller to calculate the inverse kinematic in real-time. The robot’s control involved the kinematic system, control diagram,  microcontroller, and robot programming. From the experiment, it was found that the robot manipulator was able to grip and move an object from one coordinate to another position accurately and stable with a deviation in each axis were 2-3 mm on the X, 2 mm on the Y, and 1-3 mm on the Z. As for the movement timeframe deviation that was obtained between the programmed and measured was o seconds.